Patient Pain and Function after Correction of Posterior Malleolar Malunion - Hui Zhang MD, PhD; Yaxing Li MD, PhD; Tingjiang Gan MD, PhD (Foot & Ankle Orthopaedics)
Category: Trauma; Hindfoot Introduction/Purpose: The management of an ankle malunion involving the posterior malleolus remains challenging, and only a few published studies described the operative treatment of complex posterior malleolar malunion. A transfibular approach allows for direct visualization of the articular reduction of the posterior malleolus, but the reports of its use for correcting posterior malleolar malunion are rare. This study aims to evaluate the results of the intra-articular osteotomy via a transfibular approach for correcting an ankle malunion involving the posterior malleolus. Methods: We conducted a retrospective review of 26 patients with a symptomatic malunited ankle fracture involving posterior malleolus were treated with the intra-articular osteotomy via a transfibular approach in our department. Radiographic assessments were performed using plain radiographs and computed tomographic (CT) scans. Clinical outcomes were assessed using the AOFAS ankle-hindfoot score, visual analog scale (VAS), active range of motion of ankle, and the 36-Item Short-Form Health Survey score. Results: Postoperatively, anatomic correction of articular surface and anatomic reduction of syndesmosis were achieved in all patients as judged by CT scans. No evidence of progression had been found in 18 of 26 patients (69.2%) at final follow- up. The median AOFAS score improved from 42.0 to 81.5 (P < .001). Median pain VAS score decreased from 6.0 to 1.0 (P < .001). A favorable clinical outcome was associated with a short time interval from original injury to correction surgery and a lower grade of preoperative arthritis, but not with the posterior malleolar fragment size. However, time interval, the posterior malleolar fragment size, and the grade of preoperative arthritis showed no correlation with the progression of arthritis grade after surgery. Conclusion: An intra-articular osteotomy via a transfibular approach demonstrated an improved function and pain after operative treatment of malunited ankle fracture with a displaced posterior malleolar fragment.